A Parent-Implemented Gross Motor Intervention for Young Children with Disabilities. (September 2021) - Yang, Hsiu-Wen; Meadan, Hedda; Ostrosky, Michaelene M.
Children with disabilities often experience gross motor delays. Adults, including parents, can play a crucial role in supporting children's motor development. However, a limited number of research studies have focused on building parents' capacity to support their young children's motor skill development. The purpose of this study was to examine the effects of a training and coaching program on parent implementation of prompting procedures and children's gross motor skills. A multiple-probe single-case design across three parent–child dyads was used to evaluate the effectiveness of the intervention. The findings show that parents learned how to implement prompting procedures with high fidelity. In addition, the parents reported improvements in their children's gross motor performance.